Інноваційно-освітня парадигма формування соціальної безпеки – передумова сталого розвитку - Куценко, В.; Кінаш, І.; Євтушенко, Г. (Економіка природокористування і сталий розвиток, 2020)
Розкрито роль та значення інноваційної освіти в контексті проблем соціальної безпеки. Розглянуто вплив освіти та соціальної безпеки на сталий розвиток. Окреслено місце інноваційно-освітньої парадигми у формуванні соціальної безпеки та її основні цілі. Здійснено аналіз сучасного стану освітньої сфери України. Запропоновано шляхи досягнення її стабільності та прискорення розвитку, що сприятиме сталому економічному зростанню. The article is devoted to the consideration of the important issue of the implementation of the principles of sustainable development, in the context of the introduction of innovative education and ensuring social safety. It is noted that an important result of the implementation of the process of sustainable development is social safety as a state of protection of vital rights and freedoms of citizens, as well as a system of social and political events that provides this protection. An important role in ensuring social safety and sustainable development belongs to education, which has an innovative basis. Therefore, it is important to form an innovative and educational paradigm that would contribute to the creation of an optimal socio-economic environment for social safety and sustainable development. The article highlights the problematic issues of social safety and sustainable development that are now taking place in Ukraine. Poverty, unemployment, high morbidity, rising crime – all this negatively affects the living standards of the population and the state of social safety of the country. It is noted that the strengthening of social safety largely depends on the state of human capital and the development of the educational sphere. The development of education, raising the educational level of the population acts as a catalyst for socio-economic processes, allows those working in social production to realize the achievements of scientific and technological progress and participate in its development. The innovative educational paradigm aims to provide high quality educational services, create a competitive educational environment and ensure the training of competitive specialists, which implies the establishment of a close relationship between education and business. It is also necessary to actively use the experience of developed countries to ensure the positive impact of education on the achievement of social safety and sustainable development. In this aspect, the article analyzes the current state of the educational sphere in Ukraine. The ways of achieving stability and optimal development of the educational sphere are proposed, which should contribute to ensuring economic growth on the principles of sustainable development.